Growth of Mycoplasma hyorhinis cultivar alpha on semisynthetic medium. - Gardella, R S (1995)
Serial passage of Mycoplasma hyorhinis cultivar alpha (formerly noncultivable strains) has been accomplished in modified CMRL-1066 medium with fetal bovine serum. In modified CMRL-1066 liquid medium, cultivar alpha strains grow at a similar rate and to equivalent titers when compared with BTS-7, the type strain of the species. Further experiments with BTS-7 demonstrate that the extent of growth obtained in the semidefined medium was comparable to growth in conventional mycoplasma medium. M. hyorhinis strains, including cultivar alpha strains, grow in serial passage when fetal bovine serum is replaced with bovine serum albumin, palmitic acid, and cholesterol. The results of these studies show that M. hyorhinis cultivar alpha strains are not nutritionally more fastidious than other mycoplasmas but that they are noncultivable on standard mycoplasma media because they are sensitive to high levels of inhibition activity by medium components.